Internal Control System and the Use of Digital Applications as an Effort to Prevent Fraud in Financial Institutions (A Conceptual Study and Guide for Researchers) - Coelho, Agostinho; Artati, Susi (Dinasti Accounting Review, 2025)
This study aims to conceptually examine the role of internal control systems and the use of digital applications as efforts to prevent fraud in financial institutions. The increasingly complex and sophisticated nature of fraud requires financial institutions to enhance their monitoring and control strategies. This paper presents a review of relevant literature and theories regarding internal control and digital transformation in detecting and preventing fraud. The findings indicate that an effective internal control system—which includes the control environment, risk assessment, control activities, information and communication, and monitoring—has a significant impact on reducing the likelihood of fraud. Meanwhile, the integration of technology through digital applications adds value by enabling easier transaction monitoring, real-time data tracking, and strengthening technology-based audit systems. This article is expected to serve as a conceptual guide for researchers in developing further studies related to fraud prevention in the digital era, particularly in the financial sector.